The use of applied technology in team sport - Pino Ortega, Jose; Rico-Gonzalez, Markel (Routledge research in sports technology and engineering, 2021)
The use of technology within sport is well established, most professional sport teams engage in the use of electronic performance and tracking systems. This book is the first to offer a deep and structured examination of these technologies and how they are used in a team sport setting. The Use of Applied Technology in Team Sport describes and assists researchers, academics and professionals with understanding the methodology around applied technology in sport, examining what systems track players' performance and who are the manufacturers that provide these systems. This new volume goes on to describe how to apply the systems, highlights the ways of reporting analysis information and helps the reader to know and understand the future avenues of research and development. The Use of Applied Technology in Team Sport is considered an essential guide for researchers, academics and students as well as professionals working in the areas of Applied Sport Science, Coaching, and subjects relating to Physiology, Biomechanics, Sports Engineering, Sports Technology and Performance Analysis in Sport.